Use of picric acid and iodine as electron acceptors for spectrophotometric determination of lansoprazole through a charge-transfer complexation reaction. Issue 1 (1st January 2016) - Abdulrahman, Sameer A.M.; Devi, Okram Zenita; Basavaiah, Kanakapura; Vinay, Kanakapura B.
Abstract: This article describes the development of two simple and selective spectrophotometric methods for the determination of lansoprazole (LAN), an irreversible proton pump inhibitor, in both pure drug and capsule formulations. The methods are based on the formation of charge-transfer (CT) complexes between LAN an electron donor and either picric acid or iodine as an electron acceptor. The intensely coloured products formed were quantified based on the absorption bands at 410 nm for picric acid (method A) and 360 nm for iodine (method B). The accuracy and precision of the methods were evaluated on intra-day and inter-day bases. Beer's law is obeyed in the concentration ranges of 2–32 and 0.8–12.0 μg/ml LAN for method A and method B, respectively. The molar absorptivity values, limits of detection (LOD) and limits of quantification (LOQ) have also been reported. The reaction stoichiometry for both methods was evaluated by Job's method of continuous variation and was found to be 1:1 (LAN: picric acid and LAN: iodine). The proposed methods were successfully applied to the determination of LAN in capsules with good accuracy and precision and without a detectable interference from common excipients. A statistical comparison of the methods revealed that there is no significant difference between the official method and the proposed methods.